2017
DOI: 10.1007/s00501-016-0569-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Microwave Assisted Hard Rock Cutting of Granite

Abstract: This paper describes the influence of high-power microwave irradiation on the forces needed to cut granite with a conical pick. Granite samples have been irradiated with 24 kW at 2450 MHz with an open ended waveguide. The effect of microwave treatment was assessed by linear cutting tests with a conical pick.Microwave irradiation lead to an extensive network of cracks. The linear cutting tests provide a comparison of treated and non-treated parts and show that peak as well as average forces needed for cutting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Lu et al [57] used the power of 2.1kW microwave radiation Chifeng basalt, and the use of the reduced-scale SP3-I TBM cutter to complete the rock-breaking test research, the results show that microwave radiation makes the rock-breaking volume increased significantly, disc cutter force and rockbreaking specific energy significantly reduced. Through comparative analysis, the simulation study has the same rule of change before and after microwave radiation, but due to the adjustment of microwave power and radiation time makes the input of microwave energy change, and the improvement effect in the hob force, rock-breaking, and rock-breaking specific energy is different [63] .…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [57] used the power of 2.1kW microwave radiation Chifeng basalt, and the use of the reduced-scale SP3-I TBM cutter to complete the rock-breaking test research, the results show that microwave radiation makes the rock-breaking volume increased significantly, disc cutter force and rockbreaking specific energy significantly reduced. Through comparative analysis, the simulation study has the same rule of change before and after microwave radiation, but due to the adjustment of microwave power and radiation time makes the input of microwave energy change, and the improvement effect in the hob force, rock-breaking, and rock-breaking specific energy is different [63] .…”
Section: Discussionmentioning
confidence: 99%
“…When the absorption properties of the rock are good (e.g. in basalt) this can even lead to spallation at the surface (Hartlieb 2013). Although this is spectacular, it does not lead to a deeper going or widely spread network of cracks.…”
Section: Microwave Crackingmentioning
confidence: 99%
“…Studies on basalt revealed significant microcrack differences based on power levels and distances from the antenna, with longer exposures leading to more severe cracks [41]. Subjecting granite samples to microwave treatment significantly reduced the peak and average cutting forces (~10% reduction in average cutting force from untreated to irradiated parts) [42]. It was demonstrated that the resulting temperature and stress level vary strongly depending on the input microwave irradiation parameters [43].…”
Section: Introduction 1the State Of the Artmentioning
confidence: 99%